Sunday

December 21, 2014

December 21, 2014

Posted by **Jen** on Thursday, March 1, 2007 at 6:03pm.

f(x) = log(2+x) - 4

the base is "a"

Call f(x) y

y = loga(2+x) -4

y+4 = loga(2+x)

a^(y+4) = 2 + x

x = a^(y+4) - 2

drwls, you have merely solved the equation for x.

The question was to find the "inverse", so the actual answer should be

y = a^(x+4) - 2

**Answer this Question**

**Related Questions**

math trouble - I have 2 problems I need help with using either substitution or ...

HELP! - I have no idea what the answer to this problem is, I'm given choices but...

Math - Which of the following is not a property of logarithms? A. log(A - B) = ...

Algebra help - If loga 8=2.079, loga 5=1.609, and loga 3=1.099, find the ...

math - Could you show me step by step how to find the inverse of this problem: ...

Math Exam Tuesday - My friend swears by your site so I thought I'd confirm some ...

math - Beginning with the function f(x) = log a^x, state what transformations ...

math - Beginning with the function f(x) = log a^x, state what transformations ...

algebra 2 - log(base 2)csc(x) = log(base 4)csc(4x^2) I tried doing the log(base ...

math/calculus - solve the equation loga(x-5)- loga (x+9)=loga(x-7)-loga(x+9) all...